2008
DOI: 10.1016/j.anbehav.2007.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The effects of claw regeneration on territory ownership and mating success in the fiddler crab Uca mjoebergi

Abstract: Underlying male quality is often reflected in the condition of sexually selected traits. In fiddler crabs, male success in both intra-and interspecific interactions is highly dependent on the size of the major claw. However, males are often forced to autotomize their major claw. Claw regeneration significantly altered the structure of a males' major claw in Uca mjoebergi. We found, however, that claw regeneration did not affect signal quality. Both males and females were unable to visually distinguish a regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 22 publications
(31 reference statements)
1
47
0
Order By: Relevance
“…While their original robust chelipeds are used both as display to their rivals and mates and as physical weapons in male-male contests, the regenerated slender chelipeds are considered to function as dishonest signals during the pre-fight phase and courtship behavior for females (Backwell et al 2000). Both males and females do not discriminate whether the claw is original or not in fiddler crabs (Reaney et al 2008). On the other hand, no studies have demonstrated that females choose their mates based on the major cheliped length in hermit crabs.…”
Section: Expected Function Of Regenerated Major Cheliped During Male-mentioning
confidence: 99%
See 1 more Smart Citation
“…While their original robust chelipeds are used both as display to their rivals and mates and as physical weapons in male-male contests, the regenerated slender chelipeds are considered to function as dishonest signals during the pre-fight phase and courtship behavior for females (Backwell et al 2000). Both males and females do not discriminate whether the claw is original or not in fiddler crabs (Reaney et al 2008). On the other hand, no studies have demonstrated that females choose their mates based on the major cheliped length in hermit crabs.…”
Section: Expected Function Of Regenerated Major Cheliped During Male-mentioning
confidence: 99%
“…In fiddler crabs, individuals with regenerated chelipeds have an improved performance in comparison with individuals without the cheliped during contests for territory (Backwell et al 2000, Reaney et al 2008. Although a regenerated cheliped of a male fiddler crab is lighter and less robust than the original (Backwell et al 2000, Reaney et al 2008, Lailvaux et al 2009), it allows crabs to bluff in male-male contests and for attracting potential mates (Backwell et al 2000). However, such a cheliped may not be effective in species where males aggressively use their major chelipeds as a substantial weapon during physical combat (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Claw size is considered to be the primary signal for male dominance and resource holding potential, and males with smaller claws retreat prior to physical contact more often than males with larger claws, and receive fewer visits from females (Lailvaux et al, 2009;McLain et al, 2010;Reaney et al, 2008). Following the loss of the major claw due to fighting or predator attacks, crabs can regenerate a replacement; however, males with a regenerated claw were found to be competitively inferior compared with original-clawed males (Backwell et al, 2000;Crane, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Male fiddler crabs possess a greatly enlarged (major) claw that is used as a signal during both courtship displays and prefight assessment, and as a weapon during physical contests (Jordão and Oliveira, 2001;Lailvaux et al, 2009;Reaney et al, 2008). Claw size is considered to be the primary signal for male dominance and resource holding potential, and males with smaller claws retreat prior to physical contact more often than males with larger claws, and receive fewer visits from females (Lailvaux et al, 2009;McLain et al, 2010;Reaney et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with a regenerated major cheliped are expected to improve their competitive performance compared with those without a major cheliped (e.g. Backwell et al, 2000;Reaney et al, 2008;Lailvaux et al, 2009). For example, in the fiddler crab Uca annulipes, males with a regenerated major cheliped use their chelipeds as a bluff against intruders in male-male contests for a territory (Backwell et Crustacean Research 44 al., 2000).…”
Section: Introductionmentioning
confidence: 99%